(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
This article analyzes Web3 technologies, their advantages and differences from previous generations of web technologies – Web1 and Web2. Web3 represents a new era of the Internet, which emphasizes decentralization, security and user control over data. The article discusses key aspects of Web3, such as blockchain, smart contracts and decentralized applications (dApps). It also discusses the disadvantages of Web1 and Web2, including a centralized structure and limited user control.